تحولات الشعر الجزائري المعاصر ـ من رهان اللغة الشعرية إلى رهان الجسد مقاربة لنماذج ـ - بكيس, وسيلة; زدادقة, سفيان (جامعة الوادي - University of Eloued, 2020)
شهد الشعر الجزائري المعاصر تحولات أثثت مباحثه الشعرية برؤى ومفاهيم جديدة، فكان الجسد من بينها فاتحا طروحات الذات وأسئلة الكينونة حتى أضحى "تيمة" بارزة في النص الشعري، به يكتب الشاعر الوجود، وبه يسعى لأن يحقق الذات للإنسان. فالجسد مدخل مهم لقراءة الشعر الجزائري المعاصر من منظور جديد، راهن من خلاله الشعراء على كتابة "الجسد" وقد مثَّل لها كوكبة من الشعراء الجزائريين المعاصرين الذين تشتغل عليهم مدونة هذا البحث كنماذج لمقاربة تمثلات الجسد كرهان حداثي يدل على مرحلة تحولٍ وسمت القصيدة الجزائرية المعاصرة، وإن أخذ التعبير عن هذا الجسد أبعادا متعددة فتارة كانت حادة وتارة مبتذلة، إلا أنه اكتسب قوة حضور، شحنها بطاقات إبداعية خلاقة، وتجارب قادرة على الاغواء بالقراءة والتأويل. Contemporary Algerian poetry witnessed transformations that organized its poetic discussions, so the body was a method that presented the self-propositions and questions of being until it became a prominent "theme" in the poetic text, by which the poet writes existence, and through it he seeks to achieve the human self. The body is an important entry point for reading contemporary Algerian poetry, whereby poets bet on writing the "body". This is represented in the group of contemporary Algerian poets who represent the idea of this research and they represent the representations of the body as a modernist bet indicating a stage of transformation known to the contemporary Algerian poem. The expression of this body is characterized by multiple dimensions Sometimes it was deep, and sometimes simple, but the body gained strength in presence, in creative, creative texts, and experiences capable of seducing by reading and interpreting.
مقال
Keywords: الذات؛ الجسد؛ الشعر؛ الجزائري؛ المعاصر; self; body; poem; algerian; contemporary